2007
DOI: 10.1016/j.molcel.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Chromatin-Associated Proteins MDC1 and 53BP1 in Mammalian Double-Strand Break Repair

Abstract: Phosphorylated histone H2AX ("gamma-H2AX") recruits MDC1, 53BP1, and BRCA1 to chromatin near a double-strand break (DSB) and facilitates efficient repair of the break. It is unclear to what extent gamma-H2AX-associated proteins act in concert and to what extent their functions within gamma-H2AX chromatin are distinct. We addressed this question by comparing the mechanisms of action of MDC1 and 53BP1 in DSB repair (DSBR). We find that MDC1 functions primarily in homologous recombination/sister chromatid recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
207
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(224 citation statements)
references
References 48 publications
(66 reference statements)
13
207
4
Order By: Relevance
“…To this end, we utilized cell lines that contain stably integrated reporters to assess the rates of HR (DR-GFP 10,11 ) and NHEJ. 12 --14 For NHEJ, we used cell lines containing two types of NHEJ-reporter substrates; the pCOH-CD4 that permits analysis of the NHEJ of two distal ends (separated by 3.2 kb), 12,13 and a GFP-based substrate, 14 to measure the NHEJ on closely adjacent ends, separated by only 34 bp. 14 Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we utilized cell lines that contain stably integrated reporters to assess the rates of HR (DR-GFP 10,11 ) and NHEJ. 12 --14 For NHEJ, we used cell lines containing two types of NHEJ-reporter substrates; the pCOH-CD4 that permits analysis of the NHEJ of two distal ends (separated by 3.2 kb), 12,13 and a GFP-based substrate, 14 to measure the NHEJ on closely adjacent ends, separated by only 34 bp. 14 Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…This observation is consistent with previous linkage between 53BP1 and NHEJ that 53BP1 mainly functions in NHEJ repair pathway. 55,56 How BZLF1 disrupts NHEJ is not clear at this stage. BZLF1 has been reported to bind to Ku80 through its C-terminal region.…”
Section: Discussionmentioning
confidence: 97%
“…55 Another report describes the role of H4K20me during NHEJ in mammals, whereby during the process of XRCC4-dependent NHEJ, 53BP1 recruitment depends on its interaction with dimethylated H4K20 but not on H2AX. 23 The same study also found that, alternatively, MDC1 mediates efficient HR/SCR (sister-chromatid recombination) in a manner strictly dependent on its ability to recruit γH2AX and does not require recruitment of 53BP1 or BRCA1. Therefore, these results shed light on how distinct histone tail-protein interactions promote engagement of different DSB pathways.…”
Section: Chromatin Remodeling Activities During Dna Repairmentioning
confidence: 84%
“…20 The cooperative interaction of NBS1 and ATM facilitates the further recruitment of other DNA damage response proteins, such as the mediators MDC1 (mediator of DNA damage checkpoint protein 1), 53BP1 (p53-binding protein 1) and BRCA1 (breast cancer susceptibility gene 1). [21][22][23] Remarkably, histone phosphorylation, methylation and ubiquitination cooperate in the recruitment of MDC1, 53BP1 and BRAC1, which act as adaptor proteins for recruiting additional members of the DNA damage response to sites of DNA lesions and for introducing them to the transducer kinases. All three factors share common structural features; they contain two consecutive BRCT domains (BRCA1 C-terminal domains), known as tandem BRCT domains, which are phosphoprotein-binding modules found in many proteins that regulate the DNA damage response.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%